Curcumin modulates β-catenin stabilization via targeting proteasomal deubiquitinating enzyme USP14☆ - Mengzhen Shen; Lizhe Chen; Jie Jiang; Ziye Wang; Qing Gong; Xue Zhang; Xisong Ke; Yi Qu (Pharmacological Research)
Loss of β-catenin homeostasis is tightly associated with human malignancies, modulation of β-catenin stabilization could be an attractive strategy for cancer therapy. In the present study, we demonstrated that an ancient drug curcumin was associated with selective accumulation of phosphorylated β-catenin (PBC) tagged with both ubiquitin (Ub) and Ub-like (Ubl) protein NEDD8. We further identified USP14, a deubiquitinating enzyme (DUB) in 19S proteasome, as a functional target of curcumin in modulating β-catenin. Curcumin enhances USP14-mediated PBC trapping and modulates proteasome associations, loss of USP14 significantly attenuated curcumin-increased PBC. Additionally, we found that USP14 deficiency suppressed mitotic entry and cell proliferation, targeting USP14 and PBC was essential for curcumin inhibition of cancer. Taken together, our study not only revealed the association of USP14 with PBC degradation within the proteasome, but also provided a unique small molecule curcumin targeting USP14 to modulate β-catenin for cancer therapy.